1984
DOI: 10.1159/000206421
|View full text |Cite
|
Sign up to set email alerts
|

T-Subset Abnormalities in Thalassaemia intermedia: Possible Evidence for a Thymus Functional Deficiency

Abstract: Peripheral blood T-lymphocyte subsets, evaluated by means of a series of monoclonal antibodies, were assessed in 14 patients affected by thalassaemia intermedia, 7 of them previously splenectomized. A significant reduction of T+4 cells (‘helper’ T cells) was found in almost all patients, whereas T+8 cells (‘suppressor/cytotoxic’) showed a marked increase only in splenectomized subjects. Together with these quantitative T-subset abnormalities, which seemed to be partl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…They include: impaired activity of monocytes and neutrophils [4, 5], defective activity of the complement alternative pathway [6], increased polyclonal serum immunoglobulin levels [1, 2, 3], numerical or functional alterations of different peripheral blood lymphocyte subpopulations [1, 2, 3, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]and anomalies of serum levels of cytokines and soluble antigens [3]. The pathogenic mechanism of these abnormalities is not clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They include: impaired activity of monocytes and neutrophils [4, 5], defective activity of the complement alternative pathway [6], increased polyclonal serum immunoglobulin levels [1, 2, 3], numerical or functional alterations of different peripheral blood lymphocyte subpopulations [1, 2, 3, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]and anomalies of serum levels of cytokines and soluble antigens [3]. The pathogenic mechanism of these abnormalities is not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic mechanism of these abnormalities is not clarified. Factors such as splenectomy [7, 8, 16, 19], iron overload [7, 8, 16, 19, 20], repeated exposure to foreign antigens at the time of blood transfusions [19, 21, 22]and the use of the chelating agent deferoxamine (DFO), known to have profound effects on the immune system, have been considered [12, 23]. The role of immunologic alterations on the clinical course of TM is not established, although they have been considered relevant to infectious episodes that these patients suffer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Transfusions lead to iron overload and also to immune derangements, both of which exert a negative effect on the functional integrity of the immune system in multitransfused patients with thalassaemia. There are already a large number of reports describing immune abnormalities in thalassaemia, namely defective function of polymorphonuclear neutrophils and monocytes [2,3], decrease of CD4 + cells and increase of CD8 + cells [4][5][6], diminished mitogen responses [5] and low natural killer (NK) cell activity [7,8]. These and probably other undetected abnormalities may explain the tendency for severe or unusual infections.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rats loaded with iron have been reported to have an increase in CD8 ϩ cells. However, the relationship between iron overload and the immune response is controversial, as other studies have shown that transfusional iron overload in thalassemia intermedia patients is associated with a blunted response of T cells to mitogens and with decreases in circulating CD4 ϩ cells and CD4/CD8 ratios (4). Finally, on investigating the effect of iron status on murine systemic lupus erythematosus, Leiter et al have found that iron supplementation leads to more severe renal disease and increases mortality (5).…”
mentioning
confidence: 99%
“…It binds free heme and mediates its uptake in liver cells through receptor-mediated endocytosis. Heme is then catabolized by heme oxygenase (HO) 4 into biliverdin, carbon monoxide (CO), and iron. In this way, hemopexin is thought to prevent heme-iron loss and the proinflammatory effects of free heme.…”
mentioning
confidence: 99%